The Influence of Legal Aspects and Business Ethics on Business Sustainability in the Digital Era - Riskiyatul Hasanah; Yuni Dhea Utari; Nurfitri; Delia Desvianti (Penerbit Hellow Pustaka, 2024)
This article discusses the importance of legal and ethical aspects of business in business sustainability in the dynamic and changing digital era. This research uses a normative juridical approach to examine law as a set of regulations that regulate human life. Legal aspects in digital business include dependence on digital technology, such as e-commerce, social media, and other applications, which require companies to comply with various legal requirements such as data privacy regulations, copyright, and data security to avoid legal risks that can disrupt business continuity. . The ethical aspect of business emphasizes the importance of building customer trust and loyalty as well as business reputation by interacting ethically with customers, business partners and society. Business ethics in the digital era also pays attention to aspects such as data security and privacy, transparency, accountability in artificial intelligence, honesty in digital marketing, and legal compliance. Business sustainability in the digital era requires a deep understanding of applicable laws and regulations, building a culture of compliance, implementing technology to support compliance and transparency, and collaborating with other stakeholders. Implementing good legal aspects and business ethics can increase consumer trust, strengthen reputation, and increase business value in ensuring business sustainability in the digital era. In conclusion, the importance of implementing good legal aspects and business ethics in maintaining business sustainability in the digital era not only helps companies comply with applicable regulations and regulations, but also builds trust, a good reputation and sustainable business value for the company